An integrated scheme of coal-assisted oil shale efficient pyrolysis and high-value conversion of pyrolysis oil. (1st April 2020) - Zhou, Huairong; Li, Hongwei; Duan, Runhao; Yang, Qingchun
Abstract: Shale oil produced from oil shale pyrolysis is regarded as an important alternative to crude oil. There is the conventional oil shale pyrolysis technology represented by Fushun-type, which suffers from low utilization efficiency of oil shale and low shale oil production. The development of the indirectly heated moving bed technology can solve these problems. However, this new technology requires extra heat for oil shale pyrolysis which means low pyrolysis efficiency and it also suffers from the production of low quality shale oil. The driving force for the efficient pyrolysis of oil shale and high-value conversion of shale oil calls for the involvement of high-value fuel to supply heat for pyrolysis and hydrogen source for shale oil upgradation. Coal is produced in the process of oil shale mining. A new process of coal-assisted oil shale refinery is therefore proposed in this study. Coal is used for gasification to produce syngas. Part of the syngas is used as fuel to supply additional heat for oil shale pyrolysis and the remaining syngas is used to produce hydrogen, which is then used for shale oil hydrogenation to increase the quality of shale oil. Results show that the energy efficiency of the new process is increased by 5%–24% and has a 53%–75% increase of the return on investment, comparing to those of the conventional Fushun-type technology. Graphical abstract: Image 1 Highlights: Proposed a new process of coal-assisted oil shale efficient pyrolysis and high-value conversion of pyrolysis oil. Improved energy efficiency by 5%–24% in the new process. The integrating process resulted in 53%–75% increase of return on investment.